Phenomenology of the psychological consequences of sexual abuse in children and adolescents, depending on various factors - Nutskova, E.V. (Psihologiâ i pravo, 2016)
The paper is devoted to psychological consequences of sexual abuse in children and adolescents. It presents review of domestic and foreign research of psychological injury in minors. The article gives results of complex psychological and psychiatric examination of 183 juvenile victims of sexual abuse. Psychological effects of sexual abuse in children and adolescents are identified and described on the basis of age, gender, clinical characteristics of the mental state of the victim, as well as the type and duration of the abuse. Intensity and expressiveness of post-traumatic response as well as coverage of personality spheres increase with aging. The data on the gender specificity of the sexual abuse effects suggest that girls more demonstrate internal forms, while external manifestations dominate in boys. The type and duration of sexual abuse determine a wide range of possible psychological consequences. It is noted that the severity of the psychological effects of sexual abuse in victims with mental disorders associated with the trauma is higher than in victims qualified to be mentally sane or having a mental illness, non-associated with psychologically traumatic situations. Psychological consequences exhibited by mentally sane victims show a decrease in their quality of life. Статья посвящена психологическим последствиям сексуального злоупотребления в отношении детей и подростков. Представлен обзор отечественных и зарубежных исследований проблемы психической травматизации несовершеннолетних. Излагаются результаты комплексного психолого-психиатрического обследования 183 несовершеннолетних потерпевших от сексуального злоупотребления. Выявлены и описаны психологические последствия сексуального злоупотребления у детей и подростков в зависимости от возраста, гендерной принадлежности, клинических характеристик психического состояния потерпевшего, а также типа и длительности насилия. Было установлено, что с возрастом увеличивается глубина и выраженность посттравматических реакций, охваченность различных сфер личности. Полученные данные о гендерной специфике последствий сексуального злоупотребления позволяют сделать вывод о том, что девочки в большей степени демонстрируют их интернальные формы, в то время как у мальчиков преобладают экстернальные проявления. Тип и длительность сексуального злоупотребления определяют широкий спектр возможных психологических последствий. Отмечено, что выраженность психологических последствий сексуального злоупотребления у потерпевших, страдающих психическими расстройствами, связанными с пережитой травмой, выше, чем у потерпевших, признанных психически здоровыми или имеющих психические заболевания, не связанные с пережитыми психотравмирующими ситуациями. Психологические последствия, демонстрируемые психически здоровыми потерпевшими, свидетельствуют о снижении качества их жизни.